Analisis Gaya Kepemimpinan Narendra Modi Terhadap Perubahan Kebijakan Luar Negeri Look East ke Act East - Iqbal Anta Maulana; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
In 2014 Indian Prime Minister Narendra Modi made the Act East foreign policy as a replacement for the previous policy, Look East. This policy is oriented towards strengthening the relationship between economic cooperation and maritime security in the Asia Pacific region in response to China's dominance in the Indian Ocean and South China Sea regions. This study will analyze Narendra Modi's type of leadership style to answer the question "Why did India's foreign policy change from Look East to Act East?". The purpose of this study was to determine the factors of change in India's foreign policy from Look East to Act East using leader trait analysis theory by Margarett G. Herman. This study uses a mixed method research type where the data obtained will be processed in quantitative type and qualitative type analysis using content analysis method. The result of this study show that Narendra Modi's opportunist leadership style changed India's foreign policy from Look East to Act East.